Asset Pricing and the Credit Market - Longstaff, Francis A.; Wang, Jiang (Review of Financial Studies, 2012)
This article studies the central role of the credit market. We show that the credit market facilitates optimal risk sharing by allowing less risk-averse investors to take on levered positions and consume more risk. The equilibrium amount behaves procyclically when aggregate consumption is low but countercyclically when it is high. The varying size of the credit market modifies the amount of risk sharing, which in turn influences asset prices such as expected stock returns, stock return volatility, and the term structure of interest rates. Our article provides a frictionless benchmark for the role and the behavior of the credit market. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.